General Aspects and First Progress Report on a Frame of a Research on Specific Professional Knowledge of Chemistry Teachers Associated with the Notion of Chemical Nomenclature - Perafán Echeverri, Gerardo Andrés (2014)
Within the framework of research about professional teacher’s knowledge, our business is to identify and to characterize with case study method, a kind of specific professional teacher´s knowledge of Chemistry professorate, associated to the chemical nomenclature notion. This kind of research guides the sight to the teaching contents, but it postulates the teacher as an essential actor of that knowledge, rather than ignore of the other actors (didactic community, researchers, specialists, students, etc.) our research realizes the specific construction that the teacher makes, beyond the «spontaneous epistemologies» category, between others, which seems to deny an academic and discipline character of the built knowledge by the teachers. First, we show a brief reference to the research program on professional teacher´s knowledge which frames in the development of research line about Specific Professional Teacher´s Knowledge associated with Particular Categories, which belongs to the research group «Por las Aulas Colombianas- INVAUCOL». After that, we show a short justification about the choice of the particular category: chemical nomenclature, as a studied object, besides the historical importance that it has to the professional teaching consolidation, recognizing the teacher´s specific contributions to discipline body construction of school knowledge. Finally, weset in consideration some general methodological criteria defined in this research, and we show too, some preliminary reflections derived from field work in thepresent state of the project.